The state of the late Protestant denominations - Petro Yarotskiy (Українське Pелігієзнавство, 2008)
Late Protestantism - Baptists, Pentecostals, Adventists, and Jehovah's Witnesses have existed in Ukraine for over a hundred years. Under Soviet rule, these denominations were under constant administrative pressure, subject to party-ideological criticism, atheistic propaganda. The Pentecostals were virtually banned and non-registrable, since they were forcibly annexed by evangelical Baptist Christians after the August 1945 state agreement initiated by the Moscow authorities. From the very beginning of the establishment of Soviet power in Western Ukraine (1939), Jehovah's Witnesses were declared an "anti-Soviet sect" and were therefore banned. In March 1951, an act of genocide was committed against Jehovah's Witnesses: according to the "Memorandum Note of the USSR Ministry of State Security", approved by J. Stalin's personal signature, all Jehovah's Witnesses, together with their families (7650 persons), were sent from Ukraine to eternal settlement in Siberia. without the right of return to Ukraine, and their homes and property were confiscated by the state.